(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
Two ecosystems affected by acidic pollutants (Thana Creek, Bombay and inshore area of Trivandrum, Kerala) and two other ecosystems affected by alkaline pollutants (Cola Bay, Goa and inshore area of Karwar, Karnataka) were studied for pollution effects monitoring through Foraminifera. In the Thana Creek area, Bombay, the magnitude of corrosive effect, lower—than—normal ornamentation, deepening of grooves and sutural thickenings, enlargement of pores, widening of apertures in Foraminifera were taken as indices of pollution effect. In the, Cola bay area, Goa, the environment becomes hypertrophic resulting in large—sized, robust, mostly megalospheric forms of Ammonia. Elphidium and Florilus scaphum are recorded at the proximal zone near the discharge point; miliolids in the transitional zone and dominantly smaller—sized Nonionella, Fursenkoina pontoni, Bulimina marginata at the distal zone quite far from thc discharge point where pollutants are diluted and dissipated. In the Karwär area, Karnataka, pollutant causes reduced diversity with a decrease in foraminiferal population. Moreover, there is a reduction in size followed by test wall thinning in Nonion and Ammonia, increase of agglutinated forms near shore, and dispersal and dilution of the pollutants resulting in foraminiferal abundance. In the Trivandrum area, Kerala, the effluent effect presents morphological anomalies (Operculina, Cibicides), erosion along peripheries, induced growth in last few chambers, inferred dissolution and consequent destruction of small, thin—walled forms suggested by their absence, thus leaving only the larger ones in the entire area. Living/dead ratio is negatively oriented at all sites.